Gender Equity in NEP 2020: A Pathway to Inclusive and Accessible Education - Dubey, Alpana (AG Volumes, 2025)
The National Education Policy (NEP) 2020 envisions a transformative approach to gender equity in Indian education, aiming to eliminate long-standing disparities and promote inclusivity. A key initiative under NEP 2020 is the Gender Inclusion Fund, established by the Government of India to ensure 100% enrollment of girls in schools, enhance their participation in higher education, and reduce gender gaps at all learning levels. The policy also emphasizes increasing female representation in leadership roles within educational institutions, such as principals, teachers, wardens, and physical trainers, while introducing alternative recruitment pathways for female educators, particularly in rural areas. Additionally, NEP 2020 prioritizes the safety and security of school-going girls, recognizing its importance in fostering sustained learning. By integrating gender-sensitive pedagogy and promoting equal access to education, the policy lays the foundation for an inclusive and just society. Its successful implementation holds the potential to empower individuals of all genders, ensuring their meaningful contribution to national development.